PERAN MAJELIS TAKLIM DALAM PEMBENTUKAN PEMAHAMAN FIKIH MASYARAKAT DI DESA TURUNAN KECAMATAN SAIPAR DOLOK HOLE KABUPATEN TAPANULI SELATAN - Mesran Mesran; Uba Ritonga; Irwansyah Irwansyah; Muhammad Tohir Ritonga (HIBRUL ULAMA, 2025)
This study aims to explore the role of majelis taklim (Islamic study groups) in shaping the community's understanding of fiqh (Islamic jurisprudence) in Desa Turunan, Kecamatan Saipar Dolok Hole, Kabupaten Tapanuli Selatan. The focus includes the level of fiqh comprehension among residents, the contribution of majelis taklim in enhancing this understanding, and the supporting and inhibiting factors faced in the process. This research uses a qualitative descriptive approach. Data were collected through observation and in-depth interviews with three community leaders (the village head, a local Islamic scholar, and a female religious teacher) and thirteen community members, all of whom actively participate in majelis taklim. The interviews were conducted in May 2025. Data analysis was carried out through data reduction, presentation, and conclusion drawing. The findings show that the community has a reasonably good understanding of basic fiqh, particularly in acts of worship such as ablution (wudu), prayer (shalat), and fasting (sawm). Majelis taklim plays a significant role as an informal educational forum that delivers fiqh material in a practical and contextual manner. This activity has greatly helped the community, especially women, in understanding and practicing Islamic teachings. The main supporting factors include participants' enthusiasm and communicative teaching methods, while the inhibiting factors involve limited facilities and participants' inconsistent attendance.